VALIDITY AND USABILITY OF AN AUTOMATED FALL RISK ASSESSMENT TOOL FOR OLDER ADULTS. (11th November 2018) - Sun, R; Aldunate, R; Ratnam, R; Jain, S; Morrow, D; Sosnoff, J
Abstract: Falls are a major health problem for older adults with significant physical and psychological consequences. The first step of successful fall prevention is to identify those at risk of falling. Recent technology advancement offers the possibility of objective, low-cost and easy-to-implement fall risk assessment. The present work evaluated the validity and usability of a Kinect-based self-initiated fall risk assessment system in a hospital setting. A total of 30 participants (76.6 ± 7.8 years old) enrolled in this study. The automated system includes a Kinect sensor and a computer. An onscreen Fall Risk Assessment Avatar (FRAAn) leads participant through visual and verbal instructions to complete a series of clinically validated balance and mobility tests (4-step balance test, five-time sit to stand), as well as collecting other pertinent information associated with risk of falling (fear of fall, etc.). Clinical fall risk evaluation (Timed-Up and Go -TUG, Berg Balance Scale - BBS) was also administered by a trained personnel to evaluate the validity of the FRAAn system in discriminating high-risk individuals. User experience was evaluated by the System Usability Scale (SUS). Results indicate that FRAAn-based outcome measures (postural sway metrics, and sit-to-stand speed) were highly correlated with clinical fall risk measures (TUG, BBS), and can successfully classify high-risk individuals with over 80% of accuracy. Additionally, 83% participants reported high usability (SUS > 80), indicating the system is well received among older users. This affordable, portable and automated system has potentials to allow objective fall risk assessment to be conducted more regularly among older adults